The influence of Container Availability on Company Performance and Exchange Rate as Moderator Variable at PT. Samudera Agencies Indonesia Semarang Branch - Alda Dewi Safira; Paniya - Paniya; Sugiyanta - Sugiyanta (Politeknik Negeri Semarang, 2020)
PT. Samudera Agencies Indonesia Semarang Branch’s company performance which can be explained by export volume, fluctuates every month from 2017-2020. Factors that could be the cause of these fluctuations are the container availability and exchange rates. The research aims to analyze the influence of Container Availability on export volume, and the influence of Container Availability on export volume with Exchange Rate as a moderator variable at PT. Samudera Agencies Indonesia Semarang Branch’s and to find out the contributions of all independent variables and moderator variable to dependent variable. This research is an explanatory research with quantitive approach. Simple Linear Regression Analysis and Moderator Regression Analysis method is used in this study equipped with the Descriptive Statistics Test, Classic Assumption Test, Coefficient of Determination, and T-Test. Data used in this study are secondary data which are obtained by collecting the data from Samudera Agencies Indonesia Semarang Branch and Bank of Indonesia from January 2017-February 2020. The output from this research shows that the independent variable has a significant effect on the company performance of Samudera Agencies Indonesia Semarang Branch, and exchange rate can moderate the influence between container availability and company performance. Suggestion that can be taken are paying attention to the number of container availability so they can meet exporters’ demand and export volume of the company will meet higher number at maximum, and an effective strategy to allow them to benefit from advantageous rates, as well as deal with the downside risk. Further study is needed to investigate the other factors that influence export volume/company performance